ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR: 2694K/PID.SUS/2016 TERHADAP KOSMETIK TANPA IZIN EDAR - Pratiwi, Nadia Ayu (Ensiklopedia of Journal, 2025)
Abstract: This research aims to trace the suitability of the decision to the provisions of applicable positive law, especially business actors who produce and distribute pharmaceutical preparations are required to have a distribution license as stated in Article 106 of Law No. 36 of 2009 concerning Health. The problem of this research is how the legal considerations of Supreme Court Decision Number 2694 K/PID.SUS/2016 in deciding the case of distribution of cosmetics that do not have a distribution permit. This research method uses descriptive normative research. Secondary data using primary and secondary legal materials. Data analysis is qualitative. The conclusion used for this research uses deductive logic. The results of this study, that pharmaceutical preparations, especially cosmetics in the distribution of their products in the territory of Indonesia, are required to obtain a distribution permit in accordance with the provisions of Article 106 paragraph (1) of Law No. 36 of 2009 concerning Health and Article 4 paragraph (1) of BPOM Regulation No. 21 of 2022 concerning Procedures for Submitting Notification of Cosmetics. If the Business Actor produces or distributes the pharmaceutical preparation product without a distribution permit, it is subject to a maximum imprisonment of 15 years and a maximum fine of Rp1,500,000,000 (one billion five hundred million rupiah) based on Article 197 of Law No. 36 of 2009 concerning Health.Keywords: Pharmaceutical Preparations, Cosmetics, Distribution License.